Meimei! Who is Meimei? – read, read, trade / Leow Min Hui - Leow, Min Hui (Academy of Language Studies, 2023)
Most language teachers have probably heard of the enjoyable cooperative learning game called Quiz, Quiz, Trade, advocated by Dr. Spencer Kagan (Brandt, 1990; Kagan, 1990). This game is well-liked because it encourages students to move around the classroom and engage with their peers, which increases students’ active participation in the learning process. Essentially, Quiz, Quiz, Trade is a vocabulary reinforcement method that enables students to review important vocabularies and definitions from their reading. Some instructors modified it into a question-and-answer activity to recap or strengthen students’ understanding of the knowledge. Let me briefly go over the Quiz, Quiz, Trade procedure used in language classrooms. First, every student is given a task card with different keywords or questions. It is optional to write a keyword definition or answer to the question on the back of the card. Then, students will work in pairs with their peers to accomplish the task (e.g., explain the definition of the word, answer question, etc.); students in pairs reverse the process among themselves. After completing the task, students “trade” their task card, find new partners, and the process starts over again with their new partners.